DEMOCRATIC TRADE-OFFS IN KENYA DEVELOPMENT MODEL: ELITE CAPTURE, PARTICIPATION AND GOVERNANCE OUTCOMES - Augustine, Nalianya Sungwacha; Pancasilawan, Ramadhan (Aliansi, 2026)
This paper analyses how the successive development models of Kenya, including the Vision 2030, the Big Four Agenda and the Bottom-Up Economic Transformation Agenda (BETA) have created democratic trade-offs towards achieving economic growth. The paper is based on elite capture theory and uses a comparative political-economy method, which combines qualitative research of policy texts, such as official national development plans and secondary governance indicators between 2008 and 2023. This analysis shows that, democratic erosion is not a mere policy failure, but systematically repeated development governance set up. Democratic displacement was created by vision 2030 with technocratic concentration, institutional insulation; Big Four Agenda increased this trend by squeezing accountability under executive acceleration; and BETA reorganized elite capture into localized spaces of participatory, with localized brokerage and co-optation. In all three models, the policy design varied to alter the shape of democracy, but not its content, which always arose due to the weak institutional constraints on elite power and the mischaracterization of participation and enforceable accountability. The article also adds to scholarship by applying the elite capture theory to a participatory development setting, refuting normative beliefs that inclusion is the sole means of increasing democratic legitimacy. To policy and practice, the results warn against reforms that are designed but not implemented by the institution and that the issue of economic ambition and democratic accountability can only be resolved by having power-limiting governance structures in practice.